Mempermudah Pembelajaran Ilmu Nahwu pada Abad 20 - Rahman Hakim, Arif (Jurnal Al Maqoyis, 2013)
Arabic grammar (al-Nahwu) is one of the most important disciplines to master in understanding the Islamic literatures (kutub al-turats). For its theoretical and philosophical complexity, learning nahwu becomes very difficult to the Arabic learners especially for non-Arabic speakers. Since the third century, the Arabic grammarian (al-Nahwiyyun) has tried to simplify al-Nahwu and make it easier to study (taisÄ«r al-nahwi). This effort has continued until the 20th century when the Arabic scholars, such as Ibrahim Mustafa and Syauqi Dhaif, in Middle East felt the need of simplifying nahwu to overcome the Arabic learnersâ difficulty in understanding the complex traditional nahwu books which content many rules and principles. To realize the idea, they wrote many books and presented some new concepts in simplifying nahwu.Keyword: Arabic Grammar (al-nahwu), Masterpiece, Learning.